Model ramalan keperluan doktor umum. Pakar jantung dan pakar saraf bagi hospital kerajaan di Malaysia - Sulong, Ghazali (Penerbit UTM Press, 1992)
In Malaysia, the ratio of doctors compared to the number of patients seeking treatment in government Hospitals is not proportionate. Currently the shortage of General Practitioners, Cardiologists and Neurologists is one of the major problems in Malaysia. This paper discusses some forecasting techniques using quantitative models to forecast the requirement of doctors in the future. Furthermore the growth of patients and the tenure of doctors were also analyzed. The analysis shows that the requirement for general practitioners and the specialists is linearly proportionate to the number of patients. It implies that Malaysia will encounter serious shortage of doctors in the near future if preliminary actions are not taken to prevent this shortage.